Solute ordering behaviour of L-alanine in aqueous solution: article - Rohaizat, Shafika Aina; Yusop, Siti Nurul ‘Ain; Md Azmi, Nik Salwani (2017)
L-alanine is not particularly hydrophobic and is non-polar. L-alanine is a small, naturally occurring amino acids are chiral and non-reactive hydrophobic methyl group (-CH3) as a side chain. Zwitterionic species of L-Alanine are often closely dependent on the aggregation behavior of the ionic liquids in the aqueous solution is very important from both fundamental and applied aspects. In this work, the purpose of this research is to determine the dissolution temperature of L-alanine in aqueous solution by dissolution solubility experiment method and an assessment of solute ordering behavior of L-alanine in aqueous solution, in terms of critical aggregation concentration (CAC). To determine the critical aggregation concentration, the measurement of conductivity meter have been carried out experimentally. Using conductivity method, CAC values of L-Alanine in aqueous solution were determined at different temperatures. It is known that, for aqueous solution of ionic surfactant, the critical aggregation concentration decreases at certain point and then increase with increasing temperature which creates a similar shape which can be seen from figure 7 that is the curves of conductivity vs concentration. The standard Gibbs energy of aggregation is also obtained by using van’t Hoff’s equation. The gravimetric method for solubility data of L-Alanine is also presented and discussed